Does trade liberalization reduce poverty and inequality? Empirical evidence from Pakistan - Imran Sharif Chaudhry; Fatima Imran (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2013)
This paper attempts to analyze the fact that is trade liberalization reducing poverty and income inequality in Pakistan using empirical evidence from time series data analysis. The issue of trade liberalization and its effects on the developing economies has become the hotly debated subject in recent years in all over the world. This issue has also not been analyzed so extensively in Pakistan may be due to some data constraints or due to some other reasons. Pakistan has endeavored to liberalize its trade regime and integrate its market with the world, especially since late 1980s. Pakistan made significant efforts in liberalizing its trade regime during the 1990s. The maximum tariff rate has declined from 225 percent in 1990-1 to 25 percent; the average tariff rate stands at just 11 percent compared to 65 percent a decade ago. The empirical evidence from time series regression analysis suggests that trade liberalization reduces poverty but does not having statistically significant impact on aggregate poverty and income inequality in Pakistan in short-run. In long run, trade liberalization has some strong effects on poverty and inequality. Nevertheless, other control variables - foreign remittances and gross capital formation - are found statistically significant and become highly elastic in reducing poverty and income inequality respectively during the period in short-run. The results of this study are also consistent with some other studies who concluded that trade liberalization has mixed type of effects on the lives of poor and inequality in developing countries.
Keywords: 330; trade liberalization; economic globalization; poverty; inequality; foreign remittances; Pakistan